Contrast-enhanced ultrasound for determining muscular perfusion after oral intake of L-citrulline, L-arginine, and galloylated epicatechines: a study protocol - Doll, Julian; Bürkle, Franziska; Neide, Arndt; Tsitlakidis, Stefanos; Bruckner, Thomas; Schmidmaier, Gerhard; Fischer, Christian (Medicine, 2020)
Introduction: The market for dietary supplements in the sports sector has been growing rapidly for several years, though there is still lacking evidence regarding their claimed benefits. One group is that of nitric oxide increasing supplements, so-called “NO-boosters,” which are claimed to improve the supply of oxygen and nutrients to the muscle by enhancing vasodilation. - The aim of this study was to investigate 3 of these supplements in healthy male athletes for their muscle perfusion-enhancing potential using contrast-enhanced ultrasound (CEUS). - Methods: This placebo-controlled, double-blind, randomized cross-over trial will be carried out at the Center for Orthopedics, Trauma Surgery and Spinal Cord Injury of the University Hospital Heidelberg. Three commercial NO enhancing products including 300 mg of the specific green tea extract VASO6 and a combination of 8 g L-citrulline malate and 3 g L-arginine hydrochloride will be examined for their potential to increase muscular perfusion in 30-male athletes between 18 and 40 years and will be compared with a placebo. On each of the 3 appointments CEUS of the dominant biceps muscle will be performed at rest and after a standardized resistance training. Every athlete receives each of the 3 supplements once after a wash-out period of at least 1 week. Perfusion will be quantified via VueBox quantification software. The results of CEUS perfusion measurements will be compared intra- and interindividually and correlated with clinical parameters. - Discussion: The results of this study may help to establish CEUS as a suitable imaging modality for the evaluation of potentially vasodilatory drugs in the field of sports. Other supplements could also be evaluated in this way to verify the content of their advertising claims. - Trial registration: German Clinical Trials Register (DRKS), ID: DRKS00016972, registered on 25.03.2019.